Case report: Inflammatory bowel disease in Hermansky-Pudlak syndrome type 3 due to novel variant in HPS3 - Jingqun Mai; Jingqun Mai; Zhu Zhang; Zhu Zhang; Bocheng Xu; Bocheng Xu; Shanling Liu; Shanling Liu; He Wang; He Wang; Hao Wang; Hao Wang; et al. (Frontiers in Genetics)
BackgroundHermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder with phenotypic and genetic heterogeneity, characterized by oculocutaneous albinism, bleeding diathesis, and other specific subtypes such as colitis. HPS3 is caused by biallelic mutations in HPS3. Patients with HPS3 have milder symptoms and were rarely reported to be involved in digestive disorders.Case summaryWe report a case of an 11-year-old male patient who experienced chronic diarrhea and abdominal pain for a duration of 1 year, in the absence of identifiable predisposing factors. Colonoscopy and histopathological evaluations revealed extensive colonic inflammation characterized by erosion and lymphoid hyperplasia. Given the concurrent presence of albinism, horizontal nystagmus, and inflammatory bowel disease (IBD), molecular genetic testing was conducted, which is consistent with a diagnosis of Hermansky-Pudlak syndrome (HPS). Trio-based whole-exome sequencing (Trio-WES) identified a novel homozygous nonsense variant (NM_032383.5; c.2887G > T, p.E963*) in HPS3, leading to premature termination codons and aberrant splicing-mediated mRNA decay. The patient was treated with corticosteroids and mercaptopurine for management of IBD symptoms and has been attending follow-up appointments. Currently, the patient is in clinical remission; however, there remains a potential risk of relapse.ConclusionWe present a rare case of HPS-related IBD resulting from a homozygous variant in HPS3 and provide insights into the understanding of the diagnosis and treatment of HPS3.